Calcium oxalate urolithiasis in juvenile dogs. (10th February 2021) - Saver, Alexander; Lulich, Jody P.; Van Buren, Samantha; Furrow, Eva
Abstract: Background : The features of juvenile‐onset calcium oxalate urolithiasis in dogs have not been previously reported. Methods : Calcium oxalate urolith submissions to the Minnesota Urolith Center between 2012 and 2016 were analyzed to identify those originating from juvenile (≤2 years, n = 510) or mature (7–9 years, n = 39, 093) dogs. Breed, sex, urolith salt type and urolith location were compared between groups. Breeds represented in both groups were also compared with respect to sex, urolith salt type and urolith location. Results : French (odds ratios [OR] = 14.7, p < 0.001) and English (OR = 14.3, p < 0.001) Bulldogs were overrepresented in juvenile submissions. All juvenile French and English Bulldogs were male. Across all breeds, juvenile dogs were more likely to be male (89%, p < 0.001) than mature dogs (79%). Juvenile dogs were also more likely to form dihydrate stones compared to mature dogs (33% versus 14%, respectively; p < 0.001). Breed differences were discovered in sex, urolith salt type and stone location. Conclusions : French and English Bulldogs comprise a greater proportion of juvenile calcium oxalate urolith submissions than expected based on their rarity in mature submissions. Inherited risk factors, particularly X chromosome variants, should be investigated due to the strong breed and sex predispositions identified.